The Effect of Product Innovation, Price and Marketing Capabilities on Business Performance - Wati, Mia Fajar; Muis, Indra (Green Publisher, 2025)
The title of the article is The Effect of Product Innovation, Price and Marketing Capabilities on Business Performance. This research aims to determine the influence of product innovation, selling price and marketing capability on business performance. This research is quantitative research using data obtained from questionnaires. The population used was employees of PT Dua Empat Tujuh with a total of 75 respondents. The sampling technique in this research was total sampling. Total sampling is a sampling technique where the number of samples is the same as the population. Data analysis in this research uses descriptive analysis, data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing with the help of the SPSS version 26 for Windows 2023 program. Based on the data processing that has been carried out, the following research results are obtained: product innovation has a positive and significant effect on business performance, selling price has a positive and significant effect on business performance, and marketing capability has a positive and significant effect on business performance. Furthermore, product innovation, selling prices and marketing capabilities have an influence on business performance simultaneously.